QOLP-05. OLANZAPINE FOR REFRACTORY CHEMOTHERAPY-INDUCED NAUSEA AND VOMITING IN MALIGNANT GLIOMA PATIENTS. (9th November 2020) - Patel, Mallika; Peters, Katherine; Lipp, Eric; Low, Justin; Herndon, James; Broadwater, Gloria; Johnson, Margaret; Randazzo, Dina; Kim, Jung-Young; Affronti, Mary
Abstract: INTRODUCTION: Malignant glioma (MG) patients often experience chemotherapy-induced nausea and vomiting (CINV). Olanzapine has recently been added to national anti-emesis guidelines for patients on moderately/highly emetogenic chemotherapy. In this retrospective study, we investigated the use of olanzapine for refractory-CINV (R-CINV) in MG patients. METHODS: In this chart review, we queried adult MG patients with KPS ≥ 70 who received olanzapine from January 2019-March 2020. Patients were included if they were prescribed olanzapine for CINV. Data on nausea/vomiting improvement, olanzapine dosing/schedule, number of refractory anti-emetic trials, concomitant corticosteroid use, and demographics were collected. RESULTS: We identified 21 MG patients who were prescribed olanzapine, with 9 of those patients receiving olanzapine specifically for CINV. Seven patients had WHO grade IV glioma, and 2 patients had anaplastic astrocytoma (WHO grade III). Five of 9 patients (55.6%) were male, all were Caucasian and median age was 54 years. Patients tried an average of 3 anti-emetics prior to initiating olanzapine for R-CINV. Only one patient was taking concomitant corticosteroids; which is not in concordance with national anti-emesis guidelines. Four of 9 patients (44.4%) achieved control of R-CINV with olanzapine. The olanzapine dose and key biomarkers (IDH-status, MGMT promoter methylation) were similar between those experiencing R-CINV and those without symptoms. CONCLUSIONS: In this study, we find that approximately half of patients with R-CINV achieved improved nausea and vomiting control with the addition of olanzapine. The lack of corticosteroid use for anti-emesis in MG continues to make this population challenging to manage. The relatively high success rate in patients that had failed, on average, 3 anti-emetics, suggests that olanzapine may be a potent addition to the anti-emetic toolkit for MG patients. These results inspire further large-scale research to validate this observation and define the optimal role for olanzapine in treating R-CINV in MG patients.